The Road Through Paris: Climate Change, Carbon, and the Political Dynamics of Convergence. Issue 6 (1st November 2016) - Tramel, Salena
Abstract: This article tracks the key events that set the stage for the 21st Conference of the Parties to the UN Framework Convention on Climate Change (COP21) in Paris, particularly as they relate to politics of convergence. One side of this coming together is an intersection of issues, where new terrestrial and aquatic carbon sequestration programs have blurred the margins of climate change mitigation and resource grabbing. These programs, enclosing forests, farmlands, and oceans, are likewise fused together in what can be described as an emerging 'carbon complex' that is part of the wider blue/green economy. On the reverse side, the clear intersection of issues as witnessed by radical, and historically sectoral, agrarian/social justice movements is causing them to intertwine in resistance. The realm of climate change has proven to be an exceptional space of struggle and countermovement building. Political interactions between movements have become increasingly sophisticated—requiring frameworks that address environmental, agrarian, and oceanic issues at once, as the issues have become ever more complex. Agrarian/social justice movements maintain that their agendas for food sovereignty and climate justice hinge upon exposing fault lines in the system and advocate overall system change. COP21 and its parallel side events were together a landmark moment, but part of a much more involved process, 'the road through Paris', along which movements had carved out transnational and local spaces of convergence against the backdrop of a global carbon complex.